Pengetahuan Siswa tentang Penyalahgunaan Narkoba - Indah Pusnita (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This research examinesStudent Knowledge About Drug Abuse Among Students of SMA Negeri 1 Pendopo Barat, Pendopo Barat District, Empat Lawang Regency.This study aims to obtain information about students' knowledge of drug abuse among students at SMA Negeri 1 Pendopo Barat, Pendopo Barat District, Empat Lawang Regency. The type of research used is quantitative without testing the hypothesis. And to collect information using the saturated sample technique by giving questionnaires to 93 students of SMA Negeri 1 Pendopo Barat, Pendopo Barat District, Empat Lawang Regency.The results of this study explain that the 6 (six) sub-indicators that exist with the average percentage per sub-indicator are impaired brain function and normal development, the results are yes to know (very good), intoxication (poisoning) is yes to know results ( very good), it is difficult to control oneself there are results of not knowing at all (not good), health problems have results of yes knowing (very good), negative attitudes in society have results of not knowing (quite good) and weak education there are results of yes knowing ( very good). Thus, the results of the analysis of all the research sub-indicators showed good results, and only one indicator, namely the difficulty of controlling oneself which was not good. This shows that the students of SMA Negeri 1 Pendopo Barat, Pendopo Barat District, Empat Lawang Regency, have known the dangers of drug use.